The Implementation of BCTrustAI.SL into the Automated Practices of Digital Labour Platforms to Ensure Fairness, Transparency and Accountability - Şaban İbrahim Göksal; Kristi Joamets (Bratislava Law Review, 2025)
Since digital labour platforms may infringe upon the rights of platform workers through automated decision-making and monitoring practices, the European Parliament and of the Council has adopted the Directive (EU) 2024/2831 on improving working conditions in platform work (Directive 2024/2831). This directive seeks to foster fairness, transparency, and accountability, establishing four key requirements in its algorithmic management chapter: transparency, human oversight, human review, rights to information and consultation. However, due to the abstract nature of these provisions, meeting the normative expectations of the directive poses a challenge. This paper presents the implementation of the Blockchain-Based Trustworthy Artificial Intelligence Supported by Stakeholders-In-The-Loop Model (BCTrustAI.SL) into the automated decision and monitoring practices used by digital labour platforms. It aims to discuss theoretically the validation of the concept of BCTrustAI.SL, setting the stage for subsequent technical proofs of concept.